MEMORIAL ABBASIYAH RA PANEN ILMU PENGETAHUA - Asril Asril (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
History proves the Arabs ever gave birth to a great country in the world that is the Abbasid Bani Dynasty. The greatness of this kingdom lasted between the VIII century until the middle of the XIII century AD In addition to the vastness of its territory, this kingdom is also famous for the greatness of the development of science. Various fields of science and the characters are born at this time. As in the science of religion: tafseer, qira'at, hadith, fiqh, qalam, tasauf, and language. In general science: mathematics, science falaq, art, physics, chemistry, biology, medicine, pharmacy, agriculture, anstronomy, optics, history, philosophy and other sciences. The great figures of the time were al-Farabi, al-Kindy, ibn Rushd, ibn Sina, ibn Thufail, ibn Bajah, al-Ghazali, ibn Haiyam and other figures. The rapid development of science shows the great progress achieved by the Abbasids. It seems that for now the splendor of the past will be a mere history, hope for the sake of hope does not come true because it is always less competitive with other nations.